Globalization and the Welfare State: A Review of Hans-Werner Sinn'sCan Germany Be Saved? - Snower, Dennis J; Brown, Alessio J. G; Merkl, Christian (Journal of Economic Literature, 2009)
What are the challenges that globalization makes on welfare states and how should welfare states respond? How should welfare states be designed to enable countries to reap the benefits of globalization? These are the main themes of Hans-Werner Sinn's book, Can Germany Be Saved? We view Germany as a case study of how a welfare state can go wrong in reacting to the pressures of globalization. We present two views of globalization—the “specialization view” (of Sinn) and the “Great Reorganization view” (ours)—and examine the policy implications of each for the welfare state design.